THE EFFECTIVENESS OF THE DEVELOPED NARDO MODEL IN LATERAL THINKING AMONG SECOND-YEAR INTERMEDIATE FEMALE STUDENTS IN MATHEMATICS - Inst. Dr. Halah Adnan Kadhim; Inst. Asmaa Sadiq Ghali (Journals Park Publishing, 2025)
The current research aims to recognize the impact of Nardo's developed model in lateral thinking in female students II average in mathematics, and the two researchers used the experimental design, as the research sample was divided into two groups, the experimental reached 42 female students, 42 female officers, and a number of equivalencies between the two research groups were made: (Previous achievement in mathematics, time age calculated by months, IQ test) In order to achieve the research objective, a lateral thinking test was prepared consisting of (25) A paragraph, and appropriate statistical analyses of the test paragraphs were applied while ascertaining their cychometric properties. The results showed a statistically significant difference between the two research groups and for the benefit of the experimental group in the dependent variable, and in the light of the research results some recommendations were reached. "The interest in creating the right atmosphere in the lesson and this will stimulate and elevate the motivation of learning in students and thus raise the level of lateral thinking" A number of suggestions were also made, including "a comparative study of Nardo's developed model with other teaching modules."
Keywords: Effectiveness, developed Nardo model, lateral thinking, second intermediate year, mathematics.